PELATIHAN MANAJEMEN PEMASARAN INDUSTRI RUMAH TANGGA RAKET TENIS MEJA - Tri Yulistyawati Evelina; Shinta Maharani Trievena; Ahmad Fauzi; Ayu Sulasari (Publisher UPT P2M Politeknik Negeri Malang, 2019)
The purpose of this service activity is to provide knowledge and skills for household members in managing Marketing Management. PKM methods adopted to overcome problems, namely: Pre Training, Design Training and Implementation of training The results of this service are expected to be an increase in knowledge and skills of Marketing Management and Online-Based Marketing Management and Marketing Management assistance for household members of the Malang City Table Tennis Racket Household Industry.